Who Gives? On Empathy and Impulsiveness - James Andreoni; Ann-Kathrin Koessler; Marta Serra-Garcia (ZBW – Leibniz Information Centre for Economics, 2017)
We investigate the impact of empathy and impulsiveness on charitable giving using a real donation experiment. We confirm that greater empathy predicts greater charitable giving. Contrary to recent literature, however, we find a significant negative relationship between impulsiveness and donation behavior. Specifically, when financial resources are scarce, donations are more often made by decision-makers who are able to suppress an intuitively egoistic response.
Additional information: Copyright statement: Please note this is a pre-review version of the article Who Gives? - The Roles of Empathy and Impulsiveness published in Scharf, Kimberley, and Mirco Tonin (eds.), The Economics of Philanthropy: Donations and Fundraising, pp. 49-62. 2018 Massachusetts Institute of Technology, courtesy of the MIT Press. http://mitpress.mit.edu/books/economics-philanthropy
Keywords: 330; Empathy; Impulsiveness; Charitable Giving; Donation; Pro-Social Behavior